Nuclear paraspeckle assembly transcript 1 promotes photophobia behavior in mice via miR-196a-5p/Trpm3 coupling - Zhuoan Huang; Xingshen Li; Xiaolin Wang; Jiaqi Wu; Ziyang Gong; Sulev Kõks; Minyan Wang (The Journal of Headache and Pain)
Abstract Background The long noncoding RNA, NEAT1, is recognized as a key regulator of proinflammatory gene expression; Yet, its functional role in migraine remains unexplored, despite the central role of neuroinflammatory mechanisms in migraine pathophysiology. This study examines the implication of NEAT1 in the trigeminal ganglion activation, which underlies photophobia associated with migraine. Methods Light aversion behavior was induced by intranasal injection of the TRPA1 activator, umbellulone. Male mouse behavior was assessed by the total time the mouse stays in the light between the dark and light compartments. To gain insight to the NEAT1-mediated photophobia mechanism, gene expression of candidate genes and non-coding RNAs interactions were assessed using RNA-sequencing, qPCR analysis, histology and dual-luciferase reporter gene assay. Results NEAT1 was upregulated in the trigeminal ganglion of male photophobia mice; Downregulation of NEAT1 by intravenous injection of shNEAT1 adeno-associated virus vectors attenuated NEAT1 expression and alleviated photophobia-like behavior in mice. The elevated NEAT1 expression in the trigeminal ganglion of photophobia mice corresponds to the downregulation of miR-196a-5p and upregulation Trpm3 RNA level. Predicted analysis suggested NEAT1/miR-196a-5p ceRNA network exists in photophobia mice. Indeed, knocking down NEAT1 upregulated miR-196a-5p, whilst downregulated Trpm3 gene expression level, in the trigeminal ganglion of photophobia mice. Further investigation using dual-luciferase reporter gene assay identified NEAT1 interacting with miR-196a-5p, whilst miR-196a-5p interacting with Trpm3. Similar to knocking down NEAT1, TRPM3 inhibition reduced photophobia-like behavior. Conclusion We conclude that NEAT1 is critical for promoting photophobia behavior via miR-196a-5p/Trpm3 coupling.